Pantoea agglomerans Strain EH318 Produces Two Antibiotics That Inhibit Erwinia amylovora In Vitro - Wright, Sandra A. I. (American Society for Microbiology, 2001)
Pantoea agglomerans (synonym: Erwinia herbicola) strain Eh318 produces through antibiosis a complex zone of inhibited growth in an overlay seeded with Erwinia amylovora, the causal agent of fire blight. This zone is caused by two antibiotics, named pantocin A and B. Using a genomic library of Eh318, two cosmids, pCPP702 and pCPP704, were identified that conferred on Escherichia coli the ability to inhibit growth of E. amylovora. The two cosmids conferred different antibiotic activities on E. coli DH5α and had distinct restriction enzyme profiles. A smaller, antibiotic-conferring DNA segment from each cosmid was cloned. Each subclone was characterized and mutagenized with transposons to generate clones that were deficient in conferring pantocin A and B production, respectively. Mutated subclones were introduced into Eh318 to create three antibiotic-defective marker exchange mutants: strain Eh421 (pantocin A deficient); strain Eh439 (pantocin B deficient), and Eh440 (deficient in both pantocins). Cross-hybridization results, restriction maps, and spectrum-of-activity data using the subclones and marker exchange mutants, supported the presence of two distinct antibiotics, pantocin A and pantocin B, whose biosynthetic genes were present in pCPP702 and pCPP704, respectively. The structure of pantocin A is unknown, whereas that of pantocin B has been determined as (R)-N-[((S)-2-amino-propanoylamino)-methyl]-2-methanesulfonyl-succinamic acid. The two pantocins mainly affect other enteric bacteria, based on limited testing.